Emotion beliefs: conceptual review and compendium - Kisley, Michael A.; Shulkin, Josh; Meza-Whitlatch, Margarita V.; Pedler, Rhea B. (Frontiers in Psychology, 2024)
Laypeople hold richly divergent beliefs about emotion, and these beliefs are consequential. Specific forms of belief that have been investigated include the usefulness, contagiousness, duration, dependence upon intersubjective experience, cognitively mediated properties, malleability, and hindering properties of emotion, just to name a few. Progress in this emerging sub-field of research has been hampered by the lack of a widely accepted definition of emotion belief able to capture all of these dimensions. Correspondingly, there has been a proliferation of different terminologies, constructs, and measures. The present review aims to address these obstacles by defining emotion belief, and subsequently re-considering existing constructs and measures that align with this definition. The latter is presented in the form of a comprehensive compendium of 21 different constructs and associated self-report measures that assess varying components of one’s beliefs about emotions in general and/or about their own emotions, and an additional 5 scales that were designed to measure one’s beliefs about another’s emotions. From the more unified conceptualization of emotion belief presented here, critical areas of future research are highlighted.